Pengaruh Komunikasi, Motivasi, Disiplin Kerja terhadap Kinerja Karyawan di Toko Een Underwear - Rinda, Raychal Putra Berdrian; Alam, Iskandar Ali (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study examines the influence of communication, motivation, and work discipline on employee performance at Een Underwear Store. A quantitative approach with a causal associative design was employed. The entire population of 33 permanent employees was selected as the sample using a saturated sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using SPSS version 25, applying validity and reliability tests, multiple linear regression, t-test, F-test, and coefficient of determination. The findings reveal that communication and motivation have a positive and significant impact on employee performance, while work discipline exerts a significant but negative influence. Simultaneously, the three variables significantly affect performance. These results highlight the need for managerial strategies that go beyond rigid discipline by fostering effective communication and strong motivation as key drivers of employee productivity.